Fungal volatiles influence plant defence against above‐ground and below‐ground herbivory. (25th September 2020) - Moisan, Kay; Aragón, Marcela; Gort, Gerrit; Dicke, Marcel; Cordovez, Viviane; Raaijmakers, Jos M.; Lucas‐Barbosa, Dani
Abstract: Plants have evolved resistance traits that negatively affect attackers, and tolerance traits that sustain plant growth despite herbivore damage. These mechanisms often co‐occur in a mixed‐defence strategy, balancing resistance and tolerance. These plant defences can be enhanced upon interaction with soil micro‐organisms. Here we investigated the effects of volatiles emitted by soil‐borne fungi on plant defence to insect herbivory, and on plant phenology. We exposed roots of Brassica rapa plants to volatiles emitted by four soil‐borne fungi. As a proxy of plant resistance, we assessed the performance of Pieris brassicae, a caterpillar feeding on leaves and inflorescences, and of Delia radicum, an insect root herbivore. As a proxy of plant tolerance, we compared growth of volatile‐exposed plants challenged with or without insects. Additionally, we assessed the effects on plant phenology by recording bolting time and by counting the number of buds and flowers. Plant exposure to fungal volatiles differentially affected plant resistance to above‐ and below‐ground herbivory. Performance of P. brassicae caterpillars differed between the fungal volatile‐exposed plants but was variable between experimental batches. In contrast, the effects of fungal volatiles on D. radicum performance were predominantly negative, indicating an increased plant resistance. Despite root consumption by D. radicum, root dry weight remained unchanged in infested plants compared with uninfested ones, irrespectively of the volatile exposure, suggesting compensation for the tissue loss, sometimes at the cost of undamaged above‐ground tissues. When B. rapa plants were attacked by P. brassicae caterpillars, only exposure to volatiles of some fungi led to compensation for the loss of above‐ground tissues consumed by the caterpillars, which differed between leaves and inflorescences. Furthermore, bolting was accelerated in response to volatiles of some fungi, resulting in more buds and flowers, which suggests a potential enhancement of plant fitness. Our data show that fungal volatiles can modulate the mixed‐defence strategies of B. rapa plants, balancing plant resistance and tolerance to above‐ and below‐ground herbivory. These effects may be variable and were fungus specific. Ultimately, plant fitness may be enhanced upon root exposure to fungal volatiles. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.